‘Youth Under Fire’: A Socio-Statistical Analysis of the Musketry Results of Cape Province Cadet Corps 1941-1960 (Historia, 2025)
Cadet training consisted primarily of physical fitness, military drills, and musketry. Of these activities rifle shooting is the most technical and useful military skill, with cadet participation signalling the youth’s wilful and deliberate self-militarisation. When South Africa declared war on Germany on 6 September 1939, the Union Defence Force (UDF) expanded the cadet quotas substantially in anticipation for future mobilisation. Shooting competitions took on a new urgency and significance. Teams from cadet detachments and rifle associations regularly competed in provincial, national and international shooting competitions. In South Africa, many cadet rifle competitions trace their origins to before union in 1910. The Watts Cup and Empire League Challenge (ELC) originated as challenges for cadet detachments in the Cape Colony, with cadet detachments competing in the same format from 1939 to 1960. The article presents data from the complete results of the Watts Cup and Empire League Challenge from 1941 until 1960, and data relating to support for the war among cadet officers. Analysis of this data reveals fault lines in the response of the white youth of the Cape Province from mobilisation for war to the aftermath of the pivotal 1948 elections.
Keywords: Shooting; Competition; Youth Militarisation; Second World War; Cadets